Symptomatic Bradycardia Due to Progressive Atrioventricular Block in a Young Woman Without Structural Heart Disease: A Case Report - I Gede Putu Ryan Adipathyama Perdana; Febriyanti Angghita Putri Duarsa; I Wayan Prasetya Wisuda (Rifa'Institute, 2026)
Introduction: Symptomatic bradycardia in young adults without structural heart disease is uncommon and may delay diagnosis because of its nonspecific presentation. Case Report: A 19-year-old woman presented with generalized weakness, dyspnea, chest discomfort, and recurrent syncope since adolescence. Initial electrocardiography showed second-degree atrioventricular block Mobitz type I with a ventricular rate of 36 beats per minute. Laboratory examination revealed mild hypokalemia and elevated anti-streptolysin O titer, while troponin T was normal. Transthoracic echocardiography showed normal cardiac structure and preserved left ventricular systolic function. Intravenous atropine produced minimal response, and dopamine infusion resulted only in modest heart rate improvement. Serial electrocardiography during hospitalization showed progression to complete atrioventricular block. The patient was referred to a tertiary cardiac center for further electrophysiological evaluation and pacing consideration. Discussion: This case shows that Mobitz type I atrioventricular block in young patients may not always represent a benign condition, particularly when accompanied by recurrent syncope, poor response to atropine, and progressive conduction abnormalities. Conclusion: Progressive atrioventricular block should be considered in young patients with symptomatic bradycardia despite the absence of structural heart disease. Early recognition, close monitoring, and timely pacing consideration are essential to prevent serious complications